When Does HRM 'Work' in Small British Enterprises? - Michael White; Alex Bryson (Institute for the Study of Labor (IZA), 2016)
Using nationally representative workplace data we find substantial use of high-performance work systems (HPWS) in Britain's small enterprises. We find empirical support for the proposition that HPWS have a non-linear association with employees' overall job attitude, with a positive association apparent where HPWS are used intensively. These associations are robust to factors often cited as obstacles to HPWS implementation such as informality and family ownership.
Keywords: J28; M50; M54; 330; human resource management; high-performance work system; small firms; organisational commitment; job satisfaction